Effect of rice cultivation systems on nitrogen cycling and nitrifying bacterial community structure - Thanwalee Sooksa-nguan (2018)
The system of rice intensification (SRI) has been reported to increase yields by up to 5-10 t ha-1 when compared with practices used in conventional rice cultivation. Changes in root length, root distribution and mineral nutrient cycling leading to increased crop nutrient uptake have been suggested as mechanisms responsible for the dramatic yield increases reported for SRI. In this study, we focused on the SRI practices of alternating soil flooding and draining during vegetative growth, use of young seedlings and applying compost to investigate soil microbial processes that may be involved in the SRI yield phenomenon. Nitrogen (N) mineralization, short-term nitrification, N2 fixation and denitrification potentials were measured. Potentially mineralizable N differed significantly between the two soil depths and between rice cultivation systems in soil sampled from 0 to 10 cm. Nitrification rates were consistently significantly higher in the SRI system. No differences in potential rates of denitrification or nitrogen fixation were observed between the two cultivation systems. Because nitrification rates were significantly higher in the SRI system, the ammonia-oxidizing bacterial (AOB) communities were evaluated by denaturing gradient gel electrophoresis (DGGE) of PCR amplicons as well as cloning followed by sequencing of the ammonia monoxygenase gene (amoA) from both soil depths. Cluster analysis of amoA gene revealed a clear cluster associated with SRI-managed plots in April at the 30% level of similarity. Phylogenetic analysis of amoA sequences cloned from DNA extracted from field soils revealed a few Nitrosospira-like sequences associated with the SRI system with compost applied and one Nitrosomonas-like sequence associated with the conventional rice cultivation system. Rice yields from the conventionally managed plots (5.92 and 5.47 t ha-1) were significantly higher than those obtained from the SRI-managed plots (3.67 and 3.58 t ha-1) with and without compost applied, respectively. Nematode galls were observed on roots of SRI-managed rice during the vegetative growth phase under intermittent irrigation and could be a factor in the low yields observed in the SRI plots. SRI practices resulted in yield losses at this location, most likely due to root infestations by parasitic nematodes that were able to establish when the soils were drained. Practitioners should use caution and monitor carefully for parasitic nematodes when first adopting SRI. Increased nitrification rates and changes in dominant AOB populations have the potential to change N dynamics in the SRI system that could lead to improved yields when other factors are not limiting. © 2009 Elsevier B.V.